We Are the Union: Democratic Unionism and Dissent at Boeing - DANA L. CLOUD, R. KEITH THOMAS (University of Illinois Press, 2011)
In June 1996, I attended a panel on the prospects for the labor movement at an activist conference in Chicago. On that panel was a union activist from Wichita, Kansas. His name was Keith Thomas, he worked at The Boeing Company, and he had a story to tell. The labor movement had been in a bad way through the 1980s and into the 1990s; many thousands of hardworking people found themselves with little defense against eroding union rights, falling wages and benefits, outsourcing and off-loading, and the pressure to increase productivity at all costs. Thomas, however, gave a presentation infused with optimism about the events of a strike of the International Association of Machinists and Aerospace Workers (IAMAW) against Boeing. Something incredible had happened. Boeing was ruthless in its demands during the 1995 contract negotiations for concessions. The union leadership, sluggish in its bureaucratic history and leery of a fight, prepared to take concessions. They presented two contract offers to the membership, which voted the first one down. The second contract was pitched as â€œBoeingâ€™s last, best, final offer.â€ The leadership recommended a vote. It came as a shock to everyone, except maybe the rank and file, that the membership, nearly univocally, voted it down. Thomas recounted how Boeing had been so confident that the union would sell the contract to the workers that the company had sent â€œwelcome backâ€ letters to thousands of strikers. The picket lines after the vote became rows of white flags as workersâ€”still on strikeâ€”waved their â€œwelcome backâ€ letters at passing cars and media crews. Thomas had been among a number of reformers inside his union struggling to jar union leadership into standing up for the rank and file. His group had been agitating on the shop floor for months, running campaigns for union of fice, and building a small organization called Unionists for Democratic Change. The defeat of the second contract was a sign, to the activists and to all interested in the fate of American labor, that the rank and file could become once again a force for change